Self-Efficacy as a Mediator between Practical Skills, Social Environment, and Vocational Students' Industrial Work Practice Readiness - Muhammad Zakky Putra; Wagino Wagino; Toto Sugiarto; Milana Milana; Suhendar Suhendar; Edi Setiyo (Universitas Sultan Ageng Tirtayasa, 2026)
Vocational graduates face a significant employment gap, with an Open Unemployment Rate of 8.63%, indicating a mismatch between graduate competencies and industrial demands. This study examines Self-Efficacy as a mediator between Practical Skills, Social Environmental Factors, Academic Activities, and Industrial Work Practice (Prakerin) readiness among vocational students. Using a quantitative explanatory approach, data were collected from 96 Grade XI Automotive Light Vehicle Engineering students at SMK Negeri 2 Lubuk Basung and analyzed via PLS-SEM with SmartPLS 4. Results revealed that Practical Skills exerted the strongest influence on Self-Efficacy (β=0.407; p